2021
DOI: 10.1097/ju.0000000000002028.18
|View full text |Cite
|
Sign up to set email alerts
|

Mp67-18 clinical Characteristics of Prostate Cancer Patients in West and South Africa in the Men of African Descent and Carcinoma of the Prostate (Madcap) Consortium Study

Abstract: specifically developed for use with a fiberoptic cystoscope, participants also used the ES for rigid cystoscopy, rigid and flexible ureteroscopy, and laparoscopy.CONCLUSIONS: The Endockscope System is an inexpensive and practical advance that empowers urologists in underserved countries to successfully expand their endoscopic services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent reports from the Men of African Descent and Carcinoma of the Prostate (MADCaP) Consortium Study of 2588 men with PCa in west Africa showed that the majority of men (78.9%) had high D'Amico-risk PCa [19]. Because most countries from LMICs lack guidelines on screening and early diagnosis, efforts should be made to develop best practice in PCa diagnosis and management in LMICs.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports from the Men of African Descent and Carcinoma of the Prostate (MADCaP) Consortium Study of 2588 men with PCa in west Africa showed that the majority of men (78.9%) had high D'Amico-risk PCa [19]. Because most countries from LMICs lack guidelines on screening and early diagnosis, efforts should be made to develop best practice in PCa diagnosis and management in LMICs.…”
Section: Diagnosismentioning
confidence: 99%
“…Results from the MADCaP study also showed that most men in SSA with PCa presented with moderate to severe LUTS (Table 1) [19]. As such, clinically invasive disease (Stage T3b) was more prevalent in west African men compared to men in South Africa (64.5% vs 20.2%, P < 0.001) [19].…”
Section: Introductionmentioning
confidence: 99%